RETRACTED: Quality improvement at public catering enterprises - Petržílka Slavibor; Nianko Viktoriia; Yarmoliuk Olena; Petko Stanislav; Oleksenko Roman (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001